2023
DOI: 10.3389/fnins.2023.1278183
|View full text |Cite
|
Sign up to set email alerts
|

Changes in alpha, theta, and gamma oscillations in distinct cortical areas are associated with altered acute pain responses in chronic low back pain patients

George Kenefati,
Mika M. Rockholt,
Deborah Ok
et al.

Abstract: IntroductionChronic pain negatively impacts a range of sensory and affective behaviors. Previous studies have shown that the presence of chronic pain not only causes hypersensitivity at the site of injury but may also be associated with pain-aversive experiences at anatomically unrelated sites. While animal studies have indicated that the cingulate and prefrontal cortices are involved in this generalized hyperalgesia, the mechanisms distinguishing increased sensitivity at the site of injury from a generalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Pain-induced changes in gamma oscillations in somatosensory cortex have been described (Gross et al, 2007), while noxious heat stimulation in healthy subjects was shown to increase gamma wave activity in bilateral mPFC but decrease alpha and beta wave activity in somatosensory cortex (Nickel et al, 2017). Specific patterns of altered brainwave activity involving theta, alpha and gamma oscillations have been recorded in prefrontal areas and anterior cingulate in people with chronic pain (Kenefati et al, 2023). Supporting a link between gamma oscillations and pain perception, variability in amplitude of these oscillations was found to predict inter-individual pain sensitivity (Hu and Iannetti, 2019) and others have reported links between reduced pain perception and modulated delta, beta or gamma band oscillations (Hauck et al, 2013).…”
Section: Spinal Cord and Brainstemmentioning
confidence: 88%
See 1 more Smart Citation
“…Pain-induced changes in gamma oscillations in somatosensory cortex have been described (Gross et al, 2007), while noxious heat stimulation in healthy subjects was shown to increase gamma wave activity in bilateral mPFC but decrease alpha and beta wave activity in somatosensory cortex (Nickel et al, 2017). Specific patterns of altered brainwave activity involving theta, alpha and gamma oscillations have been recorded in prefrontal areas and anterior cingulate in people with chronic pain (Kenefati et al, 2023). Supporting a link between gamma oscillations and pain perception, variability in amplitude of these oscillations was found to predict inter-individual pain sensitivity (Hu and Iannetti, 2019) and others have reported links between reduced pain perception and modulated delta, beta or gamma band oscillations (Hauck et al, 2013).…”
Section: Spinal Cord and Brainstemmentioning
confidence: 88%
“…These rhythmic patterns of synchronized neural activity flowing within and across, and linking, neighboring regions of the brain have different repetitive frequencies (delta,(1)(2)(3)(4)theta,(4)(5)(6)(7)(8)alpha,(8)(9)(10)(11)(12)(13)beta,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)gamma,, each associated with different brain states. Interestingly, there is evidence that oscillatory brain activity is linked to pain perception (Ploner and Gross, 2019;Kenefati et al, 2023;Li et al, 2023b). Pain-induced changes in gamma oscillations in somatosensory cortex have been described (Gross et al, 2007), while noxious heat stimulation in healthy subjects was shown to increase gamma wave activity in bilateral mPFC but decrease alpha and beta wave activity in somatosensory cortex (Nickel et al, 2017).…”
Section: Spinal Cord and Brainstemmentioning
confidence: 99%